Decabromodiphenyl ether (BDE-209) enhances foam cell formation in human macrophages via augmenting Toll-like receptor 4-dependent lipid uptake. (November 2018) - Zhi, Hui; Wu, Jiang-Ping; Lu, Lin-Ming; Li, Yan; Chen, Xiao-Yun; Tao, Jun; Mai, Bi-Xian
Abstract: Growing epidemiological evidence is substantiating an association between exposure to persistent organic pollutants (POPs) and incidence of atherosclerosis. Decabromodiphenyl ether (BDE-209) is a new POP which presents extensively in human populations; whether this contaminant is potentially arteriosclerotic remains unclear. In this study, we investigated the effects of BDE-209 on macrophage-derived foam cell formation, a hallmark of early atherosclerosis, using THP-1-derived macrophages incubated with oxidized low-density lipoprotein (oxLDL) as a foam cell model. The results showed that 6.25, 12.5 and 25.0 μM of BDE-209 significantly enhanced lipid accumulation inside the foam cells, in a dose-dependent manner. Further mechanism assays suggested that BDE-209 significantly increased the expression of Toll-like receptor 4 (TLR4), a signal transducing integral membrane protein mediating lipid uptake in macrophages, at both the mRNA and protein levels. In contrast, there was no significant changes for several key regulators involving in lipid efflux, lipogenesis, and lipid oxidation in macrophages. Furthermore, the augmented lipid accumulation was almost completely abrogated by treatment with an anti-TLR4 antibody. Together, these data illustrate that BDE-209 enhances oxLDL-induced macrophage foam cell formation via augmenting TLR4-dependent lipid uptake in the cells. Highlights: BDE-209 enhanced foam cell formation in human macrophages. BDE-209 promoted TLR4-dependent lipid uptake in macrophages. BDE-209 is potentially a risk factor for early atherosclerosis. One of the few reports on the mechanisms of cardiovascular toxicity of POPs.